Chewing number is related to incremental increases in body weight from 20 years of age in Japanese middle‐aged adults. (20th May 2012) - Fukuda, Hideki; Saito, Toshiyuki; Mizuta, Masato; Moromugi, Shunji; Ishimatsu, Takakazu; Nishikado, Shinobu; Takagi, Hiroshi; Konomi, Yoshihiko
Abstract : doi: 10.1111/j.1741‐2358.2012.00666.x Chewing number is related to incremental increases in body weight from 20 years of age in Japanese middle‐aged adults Background:  Eating habits are associated with both current obesity and incremental increases in body weight from young adulthood, but no study has focused on chewing number during meals among community residents. Objective:  This study focused on the relationship between chewing number and incremental increases in body weight from 20 years of age. Methods:  A total of 93 persons aged 35–61 years participated. The subjects were asked to set the device and record their chewing number during each meal on a particular day. They were also asked whether their body weight had increased by 10 kg or more since they were 20 years old. Results:  The body weight of 28 subjects (30%) had increased more than 10 kg since the age of 20 years. Total chewing number showed a relationship with such body weight increases. The odds ratio of weight increments of more than 10 kg for the lowest tertile group was 4.6 [95% confidence interval (CI), 1.3–16.2] relative to the highest tertile group (Model 1). The odds ratio of weight increments for the lowest tertile group increased to 6.3 (95% CI, 1.6–25.4) in Model 2 and to 9.1 (95% CI, 1.7–49.8) in Model 3. Conclusion:  Although this study was limited because it did not consider all risk factors, categorical chewing number was related independently to body weight increments of more than 10 kg from 20 years of age.